Descriptive classes of sets and topological functors - Banakh, T. (Український математичний журнал, 1995)
It is proved that the image of a normal functor from the Stone-Cech compactification of the projective class of sets also belongs to this class. Доведено, що образ нормального функтора від стоун-чехівської компактифікації з класу проективних множин також належить цьому класу.